Cation grain‐boundary diffusivity in SiO2‐ and MgO‐doped Al2O3. Issue 12 (21st August 2017) - Feng, Lin; Dillon, Shen J.
Abstract: Cation grain‐boundary diffusion in undoped and aliovalent‐doped Al2 O3 is characterized using Cr2 O3 as a chemical tracer. The compositional depth profiles measured by secondary ion mass spectrometry are fitted to the Whipple‐LeClaire model. The results indicate that cation grain‐boundary diffusivity is insensitive to MgO and SiO2 dopants between 1100°C and 1300°C.